2017
DOI: 10.1016/j.neurobiolaging.2017.01.026
|View full text |Cite
|
Sign up to set email alerts
|

3T hippocampal glutamate-glutamine complex reflects verbal memory decline in aging

Abstract: The hippocampus is a critical site for alterations that are responsible for age-related changes in memory. Here, we present a relatively novel approach of examining the relationship between memory performance and Glutamate-Glutamine levels using short echo time magnetic resonance spectroscopy (MRS). Specifically, we investigated the relationship between Glx (a composite of glutamate and glutamine) levels in the hippocampus, performance on a word recall task and resting state functional connectivity (RSFC). Whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 68 publications
5
13
0
Order By: Relevance
“…In a recent functional MRS study, an increase in medial PFC Glx concentration was found when participants were engaged in a task of visual imagery, relative to a control condition [20], suggesting greater Glu/Gln cycling or increased synaptic glutamate release in response to task demands. Other studies found that Glx predicted performance on a verbal memory task in both young men [4] and older adults [5]. Our study extends these results for the first time in an NHP, by showing an association between PFC Glx and cognitive flexibility.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In a recent functional MRS study, an increase in medial PFC Glx concentration was found when participants were engaged in a task of visual imagery, relative to a control condition [20], suggesting greater Glu/Gln cycling or increased synaptic glutamate release in response to task demands. Other studies found that Glx predicted performance on a verbal memory task in both young men [4] and older adults [5]. Our study extends these results for the first time in an NHP, by showing an association between PFC Glx and cognitive flexibility.…”
Section: Discussionsupporting
confidence: 85%
“…For example, NAA in cortical tissues has been found to correlate with selective aspects of cognitive performance in healthy populations [3]. Glx concentration in the hippocampus has also been shown to predict verbal memory performance in healthy adult males [4] and delayed word list recall in older adults [5]. However, Patel et al [3] caution that such approaches reveal brain/cognition associations that are typically small to moderate, and subject to a number of methodological biases.…”
Section: Introductionmentioning
confidence: 99%
“…As suggested in previous studies, it is also closely associated with the degeneration of the brain in schizophrenia patients (Zhang et al, 2012(Zhang et al, , 2014Cetin-Karayumak et al, 2019). Further, recent research mentioned that words and visuospatial memory information are conveyed across aforesaid regions via the excitatory projections of glutamatergic pyramidal neurons (Hoftman et al, 2017;Nikolova et al, 2017). More importantly, the current results are especially helpful for reminding clinical researchers to pay attention to the first-episode negative schizophrenia patients with the TT genotype.…”
Section: Main Effect Of Rs3813296 On Causality Connectivity In the Frsupporting
confidence: 66%
“…Thus, previous MRS studies showed that a decreased Glx level can be observed in neurodegenerative conditions, such as aging (Goryawala et al, 2016;Grachev et al, 2001), mild cognitive impairment and Alzheimer's disease (Antuono et al, 2001;Huang et al, 2016;Riese et al, 2015), in several GM regions including mPFC and PCC, which implies neuronal dysfunction and loss in these GM regions. Consistently, cognitive performance or cognitive symptoms have been reported to positively correlate with Glx levels in elderly people (Zahr et al, 2008) and patients with mild cognitive impairment (Nikolova et al, 2017) and Alzheimer's disease (Walecki et al, 2011). Then, an increased cortical MD, which has been observed in aging and the above-mentioned diseases (Lin et al, 2016;Ni et al, 2010;Ray et al, 2006;Weston et al, 2015), may reflect the decline in the magnitude of microstructural organization in the GM associated with aging and age-related diseases, i.e.…”
Section: Discussionmentioning
confidence: 77%